Effect of ruxolitinib supplementation in enhancing neurogenesis via gliogenesis suppression in foetal mouse brain development - Hamzah, Hamizun (2019)
JAK-STAT pathway is important in regulating gliogenesis in the brain. Dysregulation of this pathway leads to abnormality in brain development as seen in Down syndrome individuals’ predominantly low initial neuron-glia ratio in early infancy. Thus, suppression of JAK-STAT pathway would be advantageous to reverse gliogenesis towards potentially enhance neurogenesis of which may serve as an essential building block for intellectual capability in Down syndrome individuals. To date, there is only one United State Food and Drug Administration (FDA) approved drug that targets both JAK1 and JAK2 proteins. This study aims to evaluate the toxicity and ability of ruxolitinib to suppress JAK-STAT pathway in the mouse brain when being supplemented for a long term at no observed adverse effect level (NOAEL) doses of 30mg per kilogram body-weight and below. Coherently, a control group of pregnant mice fed with methylcellulose as the vehicle and another five groups of pregnant mice were treated daily with different doses of ruxolitinib (1mg, 5mg, 10mg, 15mg and 30mg per kilogram body weight) dissolved in methylcellulose via oral administration during pregnancy E7.5 through E21.5 before delivery. At P1.5 post-delivery, multiple organs were harvested from mothers such as blood, liver, kidney and spleen for toxicity screening, whereas pup whole brains were dissected for JAK proteins analysis and gene expression. Inherently, blood biochemistry showed a normal reading on liver and kidney analytes, while histology observation revealed normal cellular morphology without discernible lymphocyte infiltration in these organs thus establishing the drug, ruxolitinib is non-toxic for a long-term administration on the pregnant mouse when administering at NOAEL doses. Subsequently, western blot analysis of the P1.5 brain lysates showed no significant differences in beta-tubulin III (Tuj1) for neuronal cells in all treated groups when compared to the untreated group. However, a significant reduction in glial fibrillary acidic protein (GFAP) for glial cells was observed at 30mg/kg ruxolitinib-treated group. However, none of the phosphorylated JAK1 and JAK2 were seen reduced in P1.5 brain suggesting JAK-STAT signalling pathway may not have been effectively targeted. The findings are subjected to further analyses, and when comprehensively validated, the application of this study would institute prepregnancy prescription of ruxolitinib as supplementation to expecting mothers of late maternal age who are at high risk of having a baby with developmental disorders such as Down syndrome.